Pengaruh Kualitas Pelayanan Mopeling Sarasa Terhadap Kepuasan Masyarakat Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sukabumi - Apriliyanty, Nenden; Mulyadi, Andi; Basori, Yana Fajar FY (Jurnal Manajemen, 2022)
Motor Pelayanan Keliling Saba Rahayat Desa (Mopeling Sarasa) is one of the efforts of the Sukabumi Regency Population and Civil Registration Service in providing optimal services to help the people of Sukabumi Regency to more easily have population administration documents such as Family Cards, e-KTP, Birth Certificates , death certificates, and so on.. However, there are still problems, namely the community still has to wait for the issuance of e-KTP which is not in accordance with the Mopeling Sarasa service announcement, namely "The service is completed on the spot, can be called and one day is completed ( On Site, On Call and One Day Service). In this study, researchers used data collection techniques, namely observation, questionnaires/questionnaires, and literature study. Data analysis techniques in quantitative research use statistics, namely validity test, reliability test, correlation coefficient, coefficient of determination, regression analysis, and t test. The results showed that there was a significant effect of service quality on user satisfaction of Mopeling Sarasa.